Patients’ Medical Charts in Intensive Care Unit: A Potential Source of Nosocomial Infections - Thapa, Roshan; Thapa, Eliza; Singh, Anjana; Pokharel, Bharat Mani; Devkota, Upendra (Journal of Institute of Science and Technology, 2016)
This study was carried out to determine the degree of contamination of patients’ medical charts in ICU settings. A total of 100 medical charts were randomly selected from ICU. The swab samples were collected from outer surface of charts with sterile swabs moistened with sterile normal saline. The swabs were immediately transferred to Trypticase soy broth and incubated aerobically for 48h and then subcultured inMacConkey, Blood and Eosin-methylene blue agars. The isolates were identified by using standard microbiological and biochemical techniques. Out of 100 charts sampled, 89% charts were found to be contaminated with pathogenic or potentially pathogenic bacteria. Staphylococcus aureus was the most commonly isolated bacteria in ICU (n=32, 28.3%) followed by Citrobacter freundii (n=27, 24%), Coagulase Negative Staphylococci (CoNS) (n=23, 20.3%) and Acinetobacter spp. (n=12, 10.7%). It is concluded that medical chart contains pathogenic and potentially pathogenic bacteria. Thus, contaminated charts can act as vector of pathogenic bacteria and source of cross-infection in hospital. Journal of Institute of Science and Technology Vol. 21, No. 1, 2016, page: 48-51